Evolved Features of Artistic Motivation: Analyzing a Brazilian Database Spanning Three Decades - Varella, Marco Antonio Correa (Frontiers in Psychology, 2021)
Darwin (1871) explored the evolutionary processes underlying artistic propensities in humans. He stressed the universality of human mind by pointing to the shared pleasure which all populations take in dancing, engaging in music, acting, painting, tattooing, and self-decorating. Artistic motivation drives/reinforces individuals to engage in aesthetically-oriented activities. As curiosity/play, artistic behaviour is hypothesized as a functionally autonomous activity motivated intrinsically through an evolved, specific and stable aesthetic motivational system. I tested whether artistic motivation is rather intrinsically sourced, domain-specific, and temporally stable using a large decades-long real-life public Brazilian database of university applications. In Study I, I analysed reasons for career-choice responded by 403,832 late-adolescent applicants (48.84% women), between 1987 and 1998. In Study II, I analysed another career-choice reason question responded by 1,703,916 late-adolescent applicants (51.02% women), between 1987 and 2020. Music, Dance, Scenic Arts, Visual Arts, and Literary Studies, in combination, presented higher percentage of individuals reporting intrinsic factors (e.g., personal taste/aptitude/fulfilment) and lower proportion reporting extrinsic motives (e.g., influence of media/teacher/family, salary, social contribution/prestige) than other career groups. If artistic motivation were a recent by-product of general curiosity or status-seeking, artistic and non-artistic careers would not differ. Overall, intrinsic motives were 2.60 to 6.35 times higher than extrinsic factors; among artistic applicants’ were 10.81 to 28.38 times higher, suggesting domain-specificity. Intrinsic motivation did not differ among artistic careers, and remained stable throughout the period. Converging results corroborated a specific, stable and intrinsically sourced artistic motivation consistent with its possible evolutionary origins.